Herramienta de modelado de dominio específico (DSM) para la creación de módulos en sistemas de gestión del aprendizaje (LMS) - Montenegro Marín, Carlos Enrique; Gaona García, Paulo Alonso; Cueva Lovelle, Juan Manuel; Sajuan Martínez, Oscar (Revista Científica, 2012)
The general objective is to make domain-specific modeling for the construction of modules of learning management systems (LMS) platform independent. For this, the start point is a metamodel for the contruction a domain specific language (DSL), that with model-driven engineering (MDE) and applying the appropriate transformations are achieved from a independent model platform, deploy this model with LMS modules in moodle.